EFEKTIVITAS PENGGUNAAN LEMBAR KERJA SISWA (LKS) BERMUATAN KEISLAMAN TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA DI MA SUNAN PANDANARAN - Runtut Prih Utami; Triana Atika Zulfa (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Aim of this research is to know the effectiveness of using student worksheet in subjek matter human regulation system contains Islamic material toward the motivation and biology’s achievement of students’ cognitive in XI grade students of MA Sunan Pandanaran and to know the students’ responds. The type of this research is a quasy experimental with pretest-posttest control group design. The technique of sampling is using simple random sampling, and applying two classes, there are experiment class which using student worksheet contains Islamic material and control class which using school student worksheet. The method of collecting data use test and questionnaire. The method of analysis data use Mann Whitney U-Test, Independent Sample T-Test, and description analysis. The result of this research includes: 1) the average of learning motivation score experimental class is 79,62 and control class is 71,5. The analysis of Mann Whitney U-Test p < 0,05 means significant, so using of the student worksheet in subject matter of human regulation system contains Islamic material effective toward  learning motivation. 2) the average post-test score of experiment class is 82,9 and control class is 77,5. The analysis of Independent Sample T-Test posttest score p < 0,05 means significant, so using of the student worksheet in subject matter of human regulation system contains Islamic material effective toward  learning achievement. 3) the XI grade students giving positive responds with the percentage of the result of students’ respond in questionnaire is 79% (high category). Keywords: Islamic material, learning achievement, learning motivation, students worksheet.